Biomechanics of the clean and jerk in weightlifting national Jordanian team - Al-Khleifat, A. I.; Al-Kilani, M.; Kilani, H. A. (Journal of Human Sport & Exercise, 2019)
Seven elite national Jordanian weightlifters were videoed at 50 fields per second from the sagittal plane during the execution of the clean and jerk (C&J) on an AMTI force platform with 3 weights of submaximal lifts; low medium and high weights (35%, 65%, 85%) of their maximum. Linear and angular kinematics of the barbell with the ground reaction forces histories of the lower body were analysed using Kinova & APAS. A significant decrease was found in the maximum vertical velocity of the barbell during the second pull of the heaviest lift (p < 0.05). Maximum extension velocity of the hip joint significantly increased during the first pull of the heaviest lift (p < 0.05). Vertical velocity and maximum bar height decreased during the second pull, especially at 85%. Angle-angle diagrams of the knee and hip profile showed major differences among participants, especially at the 85% lift of their maximum.